Floral volatiles in biophytum dc. (oxalidaceae). (Funded Work) - SREESHMA L S,; BINDU R NAIR, (International Journal of Pharma and Bio Sciences, 2017)
The present study is comparative information of the essential oil composition of two commonly available species of Biophytum, B. reinwardtii and B. veldkampii. It was noted that the flowers of B. reinwardtii possessed a persistent and pleasant aroma and was intended to detect the phytochemicals responsible for this pleasant aroma. The essential oils of both the species were extracted by hydro-distillation and the components analyzed by GC-MS. The identity of the components in the extract was assigned by the comparison of their retention indices and mass spectra fragmentation patterns with the NIST08 library source. The analysis of the floral oil of both species revealed the presence of many compounds [B. veldkampii (42) and B. reinwardtii (36)], especially fatty acids such as n-Hexadecanoic acid, tetradecanoic acid and 9, 12-Octadecadienoic acid (Z, Z)-. The major component, however in both the species was n-Hexadecanoic acid [B. reinwardtii (42.32%) and B. veldkampii (51.44%)]. The remaining compounds were present in trace quantities (< 10%) in both species. The essential oil of B. reinwardtii contained certain sesquiterpenes such as alpha.-Bisabolol (5.97%), gamma-eudesmol (1.06%), .beta Bisabolene (0.69%), .alpha.-Farnesene (0.57%), Caryophyllene oxide (0.41%), Caryophyllene (0.37%), and cis alpha Bisabolene (0.30%) which are reported to be aromatic and are being widely used in cosmetic and pharmaceutical industries for various purposes. Since these compounds were absent in the essential oil of B. veldkampii, it appears that these aromatic sesquiterpenes are responsible for the pleasant aroma of B. reinwardtii flower.